Atomic Assurance The Alliance Politics of Nuclear Proliferation - Lanoszka, Alexander; Project Muse. (Cornell University Press, 2018)
"This book looks at what makes alliances so credible as to prevent nuclear proliferation, how alliances can break down and encourage nuclear proliferation, and whether security guarantors like the United States can use their alliance ties to end the nuclear efforts of their allies"--
How alliances (mis)manage nuclear proliferation -- American security guarantees during the Cold War, 1949-1980 -- West Germany, 1954-1970 -- Japan, 1952-1980 -- South Korea, 1968-1980 -- Nuclear proliferation and other American alliances.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Nuclear nonproliferation -- Government policy -- United States; Nuclear arms control -- Government policy -- United States; Nuclear arms control -- International cooperation; Nuclear nonproliferation -- International cooperation; United States -- Foreign relations -- 1945-1989 -- Case studies; Electronic books